Bartholin gland cancer. (September 2017) - Di Donato, Violante; Casorelli, Assunta; Bardhi, Erlisa; Vena, Flaminia; Marchetti, Claudia; Muzii, Ludovico; Benedetti Panici, Pierluigi
Abstract: Introduction: Bartholin gland carcinoma is an extremely rare condition. Because of its, phase III trials have not been carried out, there exists no unanimous consensus on treatment and guidelines are missing. Methods: All studies reporting cases of Bartholin cancer were collected and screened for the evaluations. Baseline characteristics of studies were extracted and were queried in a database. Results: A total number of 133 manuscripts collected were available for the review process, representing a total number of 275 reported cases. The histological type of Bartholin gland cancer was specified in 90.4% cases: 30.7% cases were squamous cell carcinoma, 29.6% adenoid cystic carcinoma, 25% adenocarcinomas. At multivariate analysis adenocarcinoma histotype and positive lymph node were statistical correlated with worse prognosis. Conclusion: Bartholin gland cancer remains a challenge for gynecologic oncologists. To better understand and treat this disease, centralization to referral centers and design of multi institutional trials is crucial.